2022
DOI: 10.1556/1886.2021.00022
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of specific combination of natural compounds against SARS-CoV-2 and its Alpha, Beta, Gamma, Delta, Kappa, and Mu variants

Abstract: Despite vaccine availability, the global spread of COVID-19 continues, largely facilitated by emerging SARS-CoV-2 mutations. Our earlier research documented that a specific combination of plant-derived compounds can inhibit SARS-CoV-2 binding to its ACE2 receptor and controlling key cellular mechanisms of viral infectivity. In this study, we evaluated the efficacy of a defined mixture of plant extracts and micronutrients against original SARS-CoV-2 and its Alpha, Beta, Gamma, Delta, Kappa, and Mu variants. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
0
15
0
4
Order By: Relevance
“…These compounds are a part of a nutritional complex -MixVwhere anti-SARS-CoV-2 efficacy was evaluated in our earlier studies and shown to be effective in simultaneous control of several cellular mechanisms involved in this viral infectivity. Among these, there was an indication of MixV's inhibitory effect on RdRp activity when using a recombinant enzyme (nsp12) and whole cell lysates [12]. Our present results show that inhibitory efficacy of this mixture expands to RdRp complex (nsp12/nsp7/nsp8) of both SARS-CoV-2 and Omicron variants, which would signal a possibility of application of micronutrients in controlling RdRp activity across a wider spectrum of viral species.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These compounds are a part of a nutritional complex -MixVwhere anti-SARS-CoV-2 efficacy was evaluated in our earlier studies and shown to be effective in simultaneous control of several cellular mechanisms involved in this viral infectivity. Among these, there was an indication of MixV's inhibitory effect on RdRp activity when using a recombinant enzyme (nsp12) and whole cell lysates [12]. Our present results show that inhibitory efficacy of this mixture expands to RdRp complex (nsp12/nsp7/nsp8) of both SARS-CoV-2 and Omicron variants, which would signal a possibility of application of micronutrients in controlling RdRp activity across a wider spectrum of viral species.…”
Section: Discussionmentioning
confidence: 61%
“…Our earlier study revealed that a combination of ascorbic acid, N-acetylcysteine (NAC) and various polyphenols could simultaneously affect key cellular mechanisms involved in SARS-CoV-2 infectivity [12]. These include inhibition of SARS-CoV-2-RBD binding to the ACE2 receptor, decreased cathepsin L and furin activity, decreased number of ACE2 receptors on human lung epithelial cells, and lower enzymatic activity of RdRp/nsp12.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kumar et al [ 18 ], magnesium ascorbate has been revealed as, among 106 other nutraceticals, the most powerful inhibitor of M PRO /3CL PRO , a key protease in SARS-CoV-2, that as a nonstructural protein participates in the replication and life cycle of the virus inside the host cell. Due to its interaction with ACE2, vitamin C is also mentioned as one of the natural compounds having the inhibitory activity against different variants of coronavirus, such as Alpha-, Beta-, Gamma-, Delta-, Kappa- or Mu-coronavirus [ 19 ]. As was shown by Ivanov et al [ 20 ], AA and its specific combinations with other natural compounds lower ACE2 expression at the protein level and at the RNA level as was proved in Human Small Airways Epithelial Cells (SAEC) and Human Microvascular Endothelial Cells (HMEC).…”
Section: Introductionmentioning
confidence: 99%
“…As was shown by Ivanov et al [ 20 ], AA and its specific combinations with other natural compounds lower ACE2 expression at the protein level and at the RNA level as was proved in Human Small Airways Epithelial Cells (SAEC) and Human Microvascular Endothelial Cells (HMEC). Goc et al [ 19 ] showed that the defined mixture of plant extracts and micronutrients with vitamin C demonstrated a highest efficacy by inhibiting the receptor binding domain (RBD), required to bind SARS-CoV-2 to ACE2 receptor. The mixture also significantly inhibited other mechanisms of viral infectivity, including the RNA-dependent RNA polymerase (RdRP), necessary for viral replication, as well as furin and cathepsin L, important for fusion of virions with host membranes and involved in viral multiplication.…”
Section: Introductionmentioning
confidence: 99%
“…Plants contain millions of natural compounds; however, traditional screening for the compounds effective against SARS-CoV-2 is very lengthy and labor-intensive. In addition, the efficacy of botanicals often depends on the intricate combination of natural compounds that makes the discovery and development of herbal treatments even more challenging [20]. Zhang DH et al (2020) demonstrated that traditional Chinese herbal therapies against viral respiratory infections are likely to have direct anti-SARS-CoV-2 compounds.…”
Section: Botanicals Targeting the Virus Replication Cyclementioning
confidence: 99%